The structure and dynamics of a water beetle community in a semipermanent wetland (Vrbenské rybníky Nature Reserve, South Bohemia) - Klečka, Jan (Jihočeská univerzita, 2008)
In my thesis I examined the structure and dynamics of a water beetle community in a semipermanent wetland in an alder carr. The results are based on three years of my field work and processing of material collected by a light trap at the study site during five years. The thesis focuses on: 1. Comparison of selectivity and efficiency of several widely used sampling methods; 2. Seasonal dynamics and effects of environmental variables on flight acitivity; 3. Spatiotemporal dynamics and effects of habitat structure and fluctuations in water levels. General patterns and relationships are highlighted.
The structure and dynamics of a water beetle community in a semipermanent wetland (Vrbenské rybníky Nature Reserve, South Bohemia)